Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 3 - Applications of Differentiation - 3.1 Exercises: 1



Work Step by Step

Using the quotient rule: $f’(x)=(\frac{u(x)}{v(x)})'=\frac{u'(x)v(x)-v'(x)u(x)}{(v(x))^2}$ $u(x)=x^2; u'(x)=2x$ $v(x)=x^2+4; v'(x)=2x$ $f'(x)=\dfrac{(2x)(x^2+4)-(2x)(x^2)}{(x^2+4)^2}=\dfrac{8x}{(x^2+4)^2}.$ $f'(0)=\dfrac{8(0)}{((0)^2+4)^2}=0.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.